Beyond the Screen: Exploring Social Media Impact on Happiness (Journal of Finance, Business and Management Studies, 2024)
By identifying the motivations behind social media use and elucidating the impact of social media on an individual's happiness, this study seeks to understand the relationship between social media use and happiness. 340 university students participated in this quantitative research. Data is gathered through a questionnaire with five point Likert scale. To analyse the data, Pearson's Correlation Coefficient was used. The study's findings indicate a relationship between university students' happiness and their use of social media. Various levels of satisfaction are found depending on the goal, such as using social media to communicate and find a buddy or connection. Additionally, the kind of internet content would have a big impact on students’ emotional responses.